Analisis Semiotika dalam Perspektif Feminisme pada Film Sore: Istri dari Masa Depan - Fauzian Yudistira; Yusida Gloriani; Hesti Muliawati (Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to: 1) describe the forms of female sacrifice depicted in the film Sore: Istri dari Masa Depan; 2) describe the meaning of female sacrifice based on an analysis of denotation, connotation and myth using Roland Barthes’s semiotics; 3) to describe the meaning of women’s sacrifice from the perspective of Simone de Beauvoir’s existential feminism. This is a qualitative study employing a descriptive analytical method and Roland Barthes’s semiotic approach. The data for this study consist of scenes, dialogue and visual elements from the film that illustrate the forms of sacrifice exhibited by female characters, with the film Sore: Istri dari Masa Depan (2025) by Yandi Laurens serving as the data source. Data collection was carried out through observation, note-taking and literature review. Furthermore, data validity was ensured through persistent observation and theoretical triangulation. Data analysis utilised the Miles and Huberman model, which encompasses data reduction, data presentation and drawing conclusions. The research findings reveal four forms of female sacrifice: emotional sacrifice; sacrifice of time and energy; physical sacrifice; and sacrifice of career and future. Sacrifice in the film is not only interpreted as a form of love, but also as a representation of gender ideology that has been normalised within society. From the perspective of Simone de Beauvoir’s existential feminism, the character Sore tends to be positioned as the Other (the Liyan). The findings of this study contribute to the field of linguistics within the realm of semiotics by demonstrating how the system of signs in films constructs ideological meanings regarding gender relations through the levels of denotation, connotation and myth.